IMPLEMENTASI MODEL PROJECT BASED LEARNING (PJBL) BERBANTU MEDIA KOMIK INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VI MATA PELAJARAN PENDIDIKAN PANCASILA - Dilla Aulia; Imam Hanafi (JISPE Journal of Islamic Primary Education, 2026)
The application of the Project-Based Learning model, supported by interactive comic media, successfully enhanced the creative thinking skills of sixth-grade students at SD Negeri 2 Karang Anyar through Classroom Action Research involving 14 students. Data collection was conducted through classroom observation and an analysis of learning outcomes, which demonstrated the development of creative thinking skills at each stage. During the pre-cycle phase, students' creative thinking levels were found to be lacking. However, mastery reached 64% in Cycle I after implementing the project-based learning model assisted by interactive comics, and this progressed to 100% in Cycle II. The researcher also recorded an increase in the class average score, which rose from 61.5 with a 28.5% mastery rate during the pre-cycle, to 72.0 with 57.1% mastery in Cycle I, and finally reached 82.1 with 100% full mastery in Cycle II. Disciplined time management using control sheets and equitable group guidance to prevent the dominance of certain students were the primary keys to the success of this action. Consequently, the researcher concludes that the implementation of the PjBL model assisted by interactive comic media is proven effective in boosting students' creative thinking skills in the Pendidikan Pancasila subject for sixth-grade students at SD Negeri 2 Karang Anyar.